Gut Microbiota Composition and Clostridioides Difficile Infection: The Potential Protective Role of Faecalibacterium Prausnitzii - Nadim Cassir; Jeanne Couturier; Johanne Delannoy; Auguste Wolfromm; Najiby Kassis Chikhani; Frédéric Barbut (Gut Microbes Reports)
The gut microbiota plays a pivotal role in Clostridioides difficile infection (CDI). We aimed to compare the composition of the gut microbiota of patients with CDI, patients asymptomatically colonized by Clostridioides difficile (CDC), patients with non-C. difficile diarrhea (NCD), and healthy controls (HCs) using 16S rRNA gene amplicon sequencing. We included 12 patients with CDI. Each CDI case was matched with four of CDC, including two with toxigenic CD strains, two patients with NCD, and two HC. Patients in each group were matched by age subgroup and antibiotic exposure. Bacterial richness was significantly higher in the HC group than in the CDC, NCD, and CDI groups. Beta-diversity analysis of the gut microbiota showed the Unifrac index to differ significantly between all groups. Relative to all other groups, the HC gut microbiota was significantly enriched by Faecalibacterium prausnitzii and Sporobacter sp. Mediterranibacterium torques, Campylobacter hominis, Blautia sp. Mobiluncus curtisii, and members of the Lachnospiraceae family. The most significantly depleted taxa in the gut microbiota of patients with CDI versus that of the HC group was F. prausnitzii. Our findings argue in favor of a potential protective role of F. prausnitzii against CDI, independently of age and antibiotic exposure.